1998
DOI: 10.1016/s0022-5223(98)70209-0
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year follow-up of coronary artery bypasses performed with and without cardiopulmonary bypass

Abstract: Despite one less graft per patient, survival and cardiac death rates were similar for the two groups. However, twice as many patients in the beating heart group required recatheterization (30% versus 16%), and 20% needed a second intervention. Only 7% of the bypass with cardioplegia group required reintervention. Limited revascularization of the beating heart provides long-term results comparable to full revascularization with cardiopulmonary bypass, but at the cost of a threefold increase in reinterventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(86 citation statements)
references
References 4 publications
2
82
0
2
Order By: Relevance
“…The results of the present study were similar to those found in an early small observational study of consecutive patients operated on between 1989 and 1990 by Gundry et al (26). They found that survival was equivalent at seven years, but OPCAB patients were almost three times more likely to require revascularization (20%) compared with CCAB patients (7%; P=0.01).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study were similar to those found in an early small observational study of consecutive patients operated on between 1989 and 1990 by Gundry et al (26). They found that survival was equivalent at seven years, but OPCAB patients were almost three times more likely to require revascularization (20%) compared with CCAB patients (7%; P=0.01).…”
Section: Discussionsupporting
confidence: 90%
“…Ascione and Angelini (5) discussed the dilemma faced by many cardiac surgeons who perform CABG. On one hand, the literature is replete with studies that emphasize the potential for reducing postoperative morbidity and length of stay with OPCAB surgery (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); on the other hand, there is continued concern regarding intraoperative myocardial ischemia, inadequate revascularization and the need for early revascularization (5,8,23,(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Regarding requirements of the experimenters in this sphere (5) there was developed miniature version of the perfusion system, tested in the first experiments on 17 rats, to which it was connected by the scheme: left middle -descending aorta, with retrograde pressurizing of blood (without occlusion of ascending aorta, in the conditions of cold cardioplegia (fibrillation of the ventricles). As a result of full heart-lung bypass in 13 cases there was observed spontaneous restoration of heart operation after 30-minute perfusion.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Ek ola rak mor ta li te ve morbi di te nin azal ma sı te me lin de, bir çok cer rah ta rafın dan özel lik le yük sek risk li has ta lar da OP CAB (off-pump ko ro ner ar ter bay pas) pro se dü rü ma liye ti avantajı kabul edilmektedir. [10][11][12] Esas ola rak gerek li et kin lik ve uzun dö nem de prog no zu için tam re vas kü la ri zas yo nun öne mi bü yük tür. 13 Dü şük mor ta li te ve mor bi di te oran la rı ile atan kalp te baypas uy gu la ma la rı nın çok sa yı da da mar lez yo nu olan has ta lar da, tam re vas kü la ri zas yon im ka nı nı zor laş -tır dı ğı gö rül mek te dir.…”
Section: Tar Tiş Maunclassified